COMPARISON OF LAWS FOR SETTLING DEBT REMAINING BANKRUPTCY BETWEEN INDONESIAN AND DUTCH COUNTRIES - Rizka Rahmawati (Warmadewa Press, 2019)
Legal products applied in Indonesia are legal products of Dutch heritage. Many of these legal products are no longer able to accommodate the legal needs of today's society. Therefore, it is necessary to reform the law, one of which is in the field of bankruptcy law. In the Netherlands, bankruptcy law has undergone a development of one regarding the settlement of debtor's remaining debts. The aims of this research is to know the legal differences in the settlement of debtor debts between Indonesia and the Netherlands, a legal comparison is needed. The method of research is legal comparison carried out by means of descriptive analysis by using a statue approach, comparative approach, conceptual approach, and historical approach. The difference in settlement of remaining debt applied in Indonesia and in the Netherlands is influenced by differences in normalized principles in bankruptcy laws in each country. Indonesia which normalizes the debt collection principle has the consequence that the remaining debt will continue to follow the bankrupt debtor until the debt is paid in full. This is different from the settlement of the remaining debt in the Netherlands that normalizes the principle of debt forgiveness, which in this principle of debt forgiveness, which in this principle the payment of the remaining debtor debt is given a maximum period of 5 years. In that period the debtor is still not able to pay off the remaining debt, the debtor can be terminated by a judge so that the debtor will be free from the remaining debts.